Application of Satellite Remote Sensing and DAPSI(W)R(M) Framework as a Tool to Assess Land Use Impacts on Urban Lakes in Sri Lanka. (September 2022) - Gunathilaka, M. D. K. Lakmali; Halwatura, Devanmini; Manawadu, Lasantha; Munasinghe, Dinuke
Urban lakes play an important role ecologically and socio-economically but are at great risk due to anthropogenic pressures. The study aimed to analyse the effects of land use and land cover change-induced lake ecosystem degradation in three urban lakes in Sri Lanka using a multi-faceted approach including: (a) satellite remote sensing, (b) geographic information system analysis and (c) a causal framework. A holistic cause–effect human–environment interaction framework (DAPSI(W)R(M)) was applied for the first time in Sri Lanka to identify measures to protect urban lake ecosystems sustainably. Results show that there was significant urban expansion during the study period with the Thalangama Lake being the most impacted regardless of its environmental protected status. Short-term mitigatory measures were proposed to reduce lake degradation, which include control of invasive species, treatment of polluted water, nutrient load monitoring and riparian buffer expansion. Sustainable city planning through the application of site-specific control measures on different scales is envisioned as a long-term solution.